Multi-stakeholder perceptions of doctoral graduate attributes: A South African perspective - Senekal, J. S.; Munnik, E.; Frantz, J. M. (South African Journal of Higher Education, 2024)
International literature reflects that doctoral graduate attributes (DGAs) include a range of academic, soft skills and personal qualities. This study described multi-stakeholder perceptions of DGAs in the South African higher education context. Fourteen semi-structured interviews were conducted with doctoral students, doctoral graduates and academic staff from four South African higher education institutions. Participants understood DGAs as the outcomes of the doctorate degree, which are developed over time. Participants’ experiences of DGAs included discussion of “academic” attributes, which align with the Qualifications Standards for Doctoral Degrees. Participants also discussed a range of personal attributes and “soft skills”. Doctoral supervisors focused on the academic attributes, whereas doctoral students and graduates gave comparatively greater weight to the personal qualities that supported the completion of their doctorates. DGAs extend beyond the traditional academic attributes, and include the “soft skills” and personal attributes that are invaluable for completion and employability. South African higher education institutions need to utilise a more comprehensive, dynamic conceptualisation of DGAs, and provide developmental support for both academic and non-academic attributes.